Differences in perceived risk of contracting sars-cov-2 during and after the lockdown in Sub-Saharan African countries - Osuagwu, U.L.; Timothy, C.G.; Langsi, R.; Abu, E.K.; Goson, P.C.; Mashige, K.P.; Ekpenyong, B.; Ovenseri-Ogbomo, G.O.; Miner, C.A.; Oloruntoba, Richard; Ishaya, T.; Charwe, D.D.; et al. (MDPI, 2021)
This study investigated risk perception of contracting and dying of SARS-CoV-2 in sub-Sahara Africa during and after the lockdown periods. Two online surveys were conducted one year apart, with participants 18 years and above living in sub-Sahara Africa or the diaspora. Each survey took four weeks. The first survey was taken from 18 April to 16 May 2020, i.e., during the lockdown. The second survey was taken from 14 April to 14 May 2021, i.e., after the lockdown. A cross-sectional study using adopted and modified questionnaires for both surveys were distributed through online platforms. Question about risks perception of contracting and dying of SARS-CoV-2 were asked. The Helsinki declaration was applied, and ethical approvals were obtained. Total responses for both surveys, i.e., both during and after the lockdown, was 4605. The mean age was similar in both surveys (18-28 years). The mean risk perception scores were higher after lockdown by 3.59%. Factors associated with risk perception of COVID-19 were survey period, age group, region of residence, and occupation. Non-health care workers had a lower risk perception of COVID-19. This first comparative study on the level of risk perception of Africans during and after the lockdown shows that one in every three and every four persons in sub-Sahara Africa felt at high risk of contracting COVID-19 and thought they could die from contracting the same, respectively.